A generic plant functional attribute set and grammar for dynamic vegetation description and analysis. - Gillison, A.N.; Carpenter, G. (1997)
Conventional method of vegetation description rarely convey the behavioural of response based information needed to describe effectively the world's vegetation for conservation and management purposes. The information required for these purposes may be derived from generic set of plant functional attributes (PFAs) as described in this paper. A grammar provides a syntactic rule base for generating and comparing individuals model or modi based on specific PFA combiantions. The method facilitaties rapid and uniform assessment of plant response to variation in the physical environment at differing spatial scales independently of species. This is illustrated by local, regional and global case studies